Aptera : the first time around (A): - Fleming, Lee, active 2022, (SAGE business cases., 2022)
Aptera is on its second life. It originally beg an as a VC-backed electric car company in the 1990s. But that first life ended badly, as the company could not raise enough money to keep going in the wake of the financial crisis (covered in the A case). The original founders have resurrected the company with a new, more capital efficient, approach to production (reviewed in the B case) and a solar panel powered design. To finance the venture, they have been considering using some of the new provisions available for equity crowdfunding, including Reg CF and Reg A+, instead of going the VC route (discussed in the C case).